IMPROVING THE METHODOLOGICAL PREPARATION OF FUTURE ELEMENTARY SCHOOL TEACHERS FOR STUDENTS LOGICAL THINKING - Maftuna Abduaziz Kizi, Ganieva (PT. Antis International Publisher, 2024)
Objective: This study explores the concept of fundamentalization in the scientific and methodological training of primary school teachers, aiming to improve educational outcomes by integrating a strong foundation of essential knowledge and skills into teacher preparation programs. Methods: The research employs a dual approach: viewing fundamentalization as the mathematization of knowledge and as the formation of a unified scientific worldview. Key factors influencing this process include the recruitment of qualified academic staff, curriculum adjustments, and the alignment of teaching methods and tools with fundamental educational principles. Results: The study identifies three main approaches to fundamentalization: as an educational content category, a didactic principle, and a quality assessment category. It highlights the importance of interdisciplinary courses and a holistic educational framework that incorporates ecological and information literacy. It also emphasizes the role of teacher professionalism in enhancing educational quality, particularly in primary education. Novelty: This research contributes a comprehensive framework for understanding fundamentalization, bridging gaps in its integration into primary teacher training programs. It offers insights into how fundamentalization can influence curriculum design, teacher preparation, and educational quality, with practical implications for improving primary education standards.